Influence of cavity-forming processes on the uplift resistance of bulb piles - Chongde Cai; Lihong Chen; Zhipeng Zhang; Xu Li; Liang Gao (Journal of Intelligent Construction)
The uplift resistances and failure modes of bulb piles with variable sections are quite different in the cutting or extruding construction modes. Through numerical simulation, the extrusion effects on the soil around the pile are estimated in this study. How the load transfers along a bulb pile is analyzed. The physical state variables of the soil around the pile are estimated, including the von Mises stress, horizontal stress, vertical stress, void ratio, displacement, and resistance. Owing to the extrusion effects, the influence range of the physical state variables increases. The greater the initial compactness of the soil around the pile is, the greater the influence range of the compaction on the physical state variables of the soil around the pile. When the compactness of the soil around the pile is high, the ultimate bearing capacity of the pile can be increased by 30% because of the extrusion effect. When the compactness is relatively small, the ultimate bearing capacity can also increase by more than 20%. The improvement in the pile bearing capacity due to the extrusion effect is reflected mainly in the enhanced plate resistance, whereas the improvement in the side resistance is not significant.